Transmission Characteristic Analysis for Disc Type Eddy Current Permanent Magnetic Governor based on Ansoft - Fang Jun; Tao Hongyan; Yu Chengbo (Jixie chuandong)
The disc type eddy current permanent magnetic governor is a new type of device for speed control,it is installed between motor and load.The torque and speed can be adjusted by magnetic flux density which relates to the gap size between the magnetic steel rotor and conductor rotor.The governor electromagnetic field is analyzed and the torque expression is established.Through the analysis,the influence factor of structure size,material property of key parts,rotation speed difference three aspects affects on the transmission characteristic are got.Then,by using the Maxwell 3D of Ansoft software,the simulation model is built and the simulation of 3D static,transient is carried out by changing influence factors separately,the air gap magnetic flux density distribution diagram and curve of each influence factor on the torque and magnetic energy utilization are obtained.By analyzing the variation reason,the conclusion is got and some references for structure size optimization and material selection of this sort of permanent magnet governor is provided.